Sulphite oxidase as key enzyme for protecting plants against sulphur dioxide - Lang, Christina; Wirtz, Markus; Hell, Rüdiger (Plant, cell & environment, 2007)
Sulphur dioxide (SO2) is known as a strongly damaging air pollutant. After conversion to sulphite in aqueous solution, it becomes a strong nucleophilic agent that attacks numerous compounds in the cell. Therefore, plants have developed a mechanism to control sulphite levels. Recently, we have cloned and characterized the enzyme sulphite oxidase (SO) from Arabidopsis thaliana. Yet, its physiological role remained unclear. Here, we describe results demonstrating that SO is essential for detoxifying excessive amounts of sulphite in the cell which is important for the survival of the plant. T-DNA-tagged A. thaliana plants lacking the enzyme showed a decrease in vitality during SO2 fumigation and a change in their S-metabolites. The same was found with RNA-interference (RNAi) plants that were generated for tobacco. On the contrary, over-expression of SO helped the plant to survive SO2 concentrations that are detrimental for non-transformed wild-type (WT) plants, as was shown with poplar plants which are known to be particularly sensitive to SO2. Fumigation induced the expression of the enzyme as demonstrated by promoter-reporter gene fusion, by immunoblot analysis of SO-protein and by induction of enzyme activity. This implies that SO, as an otherwise constitutively expressed protein, is under additional control by SO2 in the environment.